Evaluasi Stabilitas Beta-Karoten pada Red Palm Oil (RPO) Selama Penyimpanan dengan Analisis Spektrofotometri UV-Vis - Indria Mahgfirah; Kiki Kristiandi; Hidayat Asta; Mia Audina; Evelin Agusti (Journal of Food Security and Agroindustry, 2026)
Beta-carotene is the major carotenoid compound in red palm oil (RPO) and serves as a provitamin A source; however, it has low stability against environmental factors during storage. This study aimed to analyze changes in beta-carotene content in RPO from Sambas, West Kalimantan, during storage using the UV–Vis spectrophotometric method. Samples were analyzed on day 1 and day 7 using iso-octane as the solvent, and measurements were performed at a maximum wavelength of 446 nm. The results showed that the average beta-carotene content decreased from 188.59 ppm on day 1 to 179.46 ppm on day 7, corresponding to a reduction of 4.84%. This decrease indicated beta-carotene degradation, which was influenced by oxidation, light exposure, and temperature during storage. Nevertheless, the relatively small reduction suggested that the storage conditions were still sufficient to maintain beta-carotene content in RPO. Therefore, RPO should be stored in dark containers, such as amber bottles. These findings are consistent with previous studies reporting that carotenoid degradation in palm oil occurs gradually during storage. Thus, controlling storage conditions is essential to maintain the stability and nutritional value of RPO.